The Effects Of Ylang-Ylang (Cananga Odorata) Essential Oil On Behavioural Symptoms And Plasma Biomarkers In Long-Term Care Residents With Dementia - Sivasankar, Thisha Abirami (2023)
This study examines the effectiveness of diffused ylang-ylang essential oil based on dementia-related behavioural assessment tools and biochemical analysis using blood samples of persons with BPSD. A pre-post quasi-experimental study was conducted over two months in three nursing homes with persons with dementia (n=28).